2016
DOI: 10.3329/ijns.v5i1.28605
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Yield Components of Wheat as Influenced by Sowing Date and Humic Acid

Abstract: In order to investigate the effect of seed sowing date and humic acid foliar application on some agronomic traits of bread wheat an experiment was conducted in Islamshahr, Iran during 2013 growing season. The experimental design was a complete randomized block design arranged in factorial with three replications. The first factor was included two sowing date (middle of November and middle of December) and the second factor was included three humic acid levels (0, 4 and 8 liter ha -1 ). The results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The stimulating effect of both HA and Zn is partly associated with the higher uptake of mineral nutrients (33). Similarly, positive effects of HA and Zn application on the yield of different crops such as pearl millet (34), wheat (30,31,35,36) and sunflower (37) have been reported in other studies. In some studies, it has been shown that 5 or 10 kg Zn ha -1 ( 25-50 kg ZnSO ⁓ 4.7H2O) application is sufficient for high yield of cereals (38,39).…”
Section: Resultssupporting
confidence: 65%
“…The stimulating effect of both HA and Zn is partly associated with the higher uptake of mineral nutrients (33). Similarly, positive effects of HA and Zn application on the yield of different crops such as pearl millet (34), wheat (30,31,35,36) and sunflower (37) have been reported in other studies. In some studies, it has been shown that 5 or 10 kg Zn ha -1 ( 25-50 kg ZnSO ⁓ 4.7H2O) application is sufficient for high yield of cereals (38,39).…”
Section: Resultssupporting
confidence: 65%
“…The overall effect of humic acid (HA) application showed a positive response, significant or insignificant, to spraying of 2.4 kg/ha HA compared to the control. Several researchers reported significant positive effects of HA on grain yield (Antoun et al, 2010, Khan et al ,2010and Manzoor et al ,2014, 1000-grain weight (Knapowski et al ,2015 andAL-Erwy et al ,2016), number of tiller plant (Yasin andEL-Sobky,2017 andBaqir andZeboo, 2019) biological yield (Kandil et al ,2016 andDincsoy andSonmez, 2019) and number of grains/spike (Doroodian et al ,2015 and Yassin and EL-Sobky 2017) of wheat plants. However, durum wheat cultivars showed differential response to application of HA (Fig 1 and 2, a, b and c) where both cultivars Bani Sweif6 and Sohag3 showed a positive response to HA application compared to control with regard to grain yield, while Casino cultivar revealed a negative response to HA spraying.…”
Section: Discussionmentioning
confidence: 99%